The Usefulness of the cortisol:testosterone ratio in assessing the catabolic and anabolic balance of athletes - Judek, Roksana; Latour, Emilia; Latour, Marianna; Melnyk, Bohdan; Rygielski, Artur (Quality in Sport, 2024)
Introduction and purpose: The balance between catabolic and anabolic processes is crucial for achieving optimal athletic performance and maintaining the health of athletes. The cortisol-to-testosterone ratio (C/T) is a commonly used indicator to assess this balance, as it allows for monitoring the equilibrium between these two hormones. This literature review aims to evaluate the utility of T/C ratio in monitoring this balance, providing insights into its relevance for athletic training and performance. The paper is based on a relevant review of literature about the practical aspects of measuring the C/T ratio and its correlation with athletic performance, recovery, overtraining, and training adaptation were analyzed. Description of the state of knowledge: The cortisol-to-testosterone ratio is a useful indicator for evaluating between catabolic and anabolic states in athletes. It can be practically applied to fine-tune training regimens and help prevent overtraining.However, its effectiveness is dependent on various factors, including individual variability and the influence of external factors such as sleep. Summary: The C/T ratio remains a valuable tool for assessing the metabolic-anabolic balance in athletes. Practical aspects of measurement and interpretation are essential for its effective application. Continued research is needed to refine the use of this biomarker across different sports and training contexts.